Development of Entrepreneurial Orientation - Eka Zahra Solikahan; Ali Mohammad (AIBPM Publisher, 2019)
The Entrepreneurial orientation (EO), is a company activity that are related to proactive decision-making practices that pay attention to innovative strategies, risk-taking and exploiting market opportunities. This study aims to explain the development of the EO with a qualitative approach with the literature study method. Results obtained, EO was first introduced by miller in 1983, stating the importance of innovation, risk taking, productiveness in the EO concept, later developed by Morris and Paul (1987), and Merz and Sauber (1995). In 1996 Lumpkin and Dess perfected the EO concept of Miller (1983) by adding autonomy and competitive aggressiveness in measuring EO. But in its development to date, EO measurements based on several earlier studies EO measurements combine between the studies of Miller (1983) and Lumpkin and Dess (1996).